The Implementation of Patient Information System Technology on Employee Effectiveness in Chasbullah Abdulmadjid Hospital - Sri Utami; Panji Madya Ramdani; Bambang Junadi; Sari Masshitah (Kusuma Negara Business School, 2020)
This study aims to determine the effect of patient information system technology on the work effectiveness of employees of Chasbullah Abdulmadjid Hospital Bekasi City. This research is a quantitative study with a sample of 32 people. The results of the study indicate that the patient's information system technology has an influence on the work effectiveness of the employees of Chasbullah Abdulmadjid Hospital Bekasi City 84.6%. Based on the calculation of the coefficient of determination, the result is 71.5%, which shows the effect of patient information system technology on the work effectiveness of employees by 71.5% and the remaining 28.5% is influenced by other factors. Based on the calculation of simple linear regression analysis, the equation Y = 6,046 + 0,842X is obtained, which shows that without the patient information system technology, the work effectiveness is 6,064. And if X increases by 1 point or every increase in patient information system technology by 1, it will increase the work effectiveness of employees by 0.842 and vice versa. And have a positive relationship.